Mechanisms formation of electron-hole trap centers in LiKSO4 crystall - T.N. Nurakhmetov; Zh.M. Salikhodzha; A.M. Zhunusbekov; A.Zh. Kainarbay; D.H. Daurenbekov; T.T. Alibay; B.M. Sadykova; K.B. Zhangylyssov; B.N. Yussupbekova; D.A. Tolekov (Eurasian Journal of Physics and Functional Materials, 2021)
The mechanisms of creation of electron-hole trapping centers in LiKSO4 have been investigated by the methods of vacuum and thermal activation spectroscopy. It is shown that electron-hole trapping centers are formed during the trapping of electrons by anionic complexes and localization of a hole in the lattice in the form of the radical SO−4 . The appearance of phosphorescence at 3.0-3.1 eV, 2.6-2.7 eV and 2.3-2.4 eV confirms the creation of electron-hole trap centers.